Analysis of the Application of Ferrosement Method to Earthquake-Resistant Houses Affects Cost - Moch Afrizal Subakti; Yudi Setio Prabowo (Publikasi Indonesia, 2024)
In the context of building earthquake-resistant houses, the use of ferrosement technology can be an effective solution to face unique environmental challenges. The sustainability, strength, and earthquake resistance provided by ferrosement make it an attractive option in an effort to improve the quality and safety of buildings in areas prone to earthquakes. This study will use a comparative method to analyze the cost needs of building earthquake-resistant houses using Ferromen technology. The total cost of materials for ferrosemen houses with type 7 x 6 amounted to 69,783,571,131. The use of ferrrosemen technology in home construction offers significant cost efficiency potential compared to traditional construction methods. This is mainly because the raw materials used in fermenting, such as local soil and fiber, are generally more affordable and widely available. 2. Focus on Strength Ferrocement technology focuses strength on the foundation of the house which uses an inverted T foundation with woven concrete iron, which is much stronger than the river stone foundation. Although further research and local adaptation are still needed, the use of ferrrosement technology is promising as a more economical alternative in house construction. This can be a sustainable solution to improve access to affordable housing for people in various regions, especially in developing countries. However, it is important to consider factors such as soil conditions, climate, and availability of local resources in effectively implementing this technology.